Application of Fuzzy Techniques for Determining the Operating Speed Based on Road Geometry - D’Andrea, Antonino; Pellegrino, Orazio (Promet - Traffic&Transportation, 2012)
The operating speed is certainly one of the most important variables in the management of road safety. Its determination has been refined in the last few years by means of experimental analyses that have also sanctioned its strong link with the context in which speed surveys are carried out. In fact, even though all the algorithms proposed have a very simple analytical structure, it has been noted that they can never have a general character and thus be applied without losing a certain amount of reliability.Moreover, the technological development today achieved would allow for recording in a complete way of the road environment as modern measuring instruments provide in digital format and in an economically convenient manner a great amount of data.As such, the aim of this work is to propose a methodology that allows not only the ordering and classification of numerous important data but one that is able to recognise the presence of links of dependence between unknown variables a-priori or, in any case, of difficult analytical characterisation. The technique of clustering used in order to achieve this is preliminary to the organisation of a general fuzzy model that takes into account certain variables of input linked to the geometry of the road and to the visibility and that provides as output the operating speed.Such model has been applied to a rural road located in Messina (Italy) and the results achieved, tested with experimental surveys as well as with algorithms present in literature, are very encouraging and invite deeper exploration of the study.